A NOTE ON THE DISTRIBUTION AND HABITAT PREFERENCE OF Cyclotus longipilus VON MARTENS, 1865 FROM THE MAROS KARST AREA OF SOUTH SULAWESI (GASTROPODA: CYCLOPHORIDAE) - Ristiyanti M. Marwoto (Treubia, 2007)
-